Pengaruh Pemberian Ekstrak Etanol Buah Gandaria (Bouea macrophylla Griff.) Terhadap Profil Lipid Tikus Putih (Rattus norvegicus L.) Yang Diinduksi Karbon Tetraklorida (CCI4) - Putri, Nesya Destika; Febriani, Husnarika (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to evaluate the effect of ethanolic extract of gandaria fruit (Bouea macrophylla Griff.) on the lipid profile of male white rats (Rattus norvegicus L.) induced with carbon tetrachloride (CCl₄). The study highlights the potential hypolipidemic activity of the extract by measuring levels of total cholesterol, triglycerides, Low Density Lipoprotein (LDL), and High Density Lipoprotein (HDL). A Completely Randomized Design (CRD) was employed, involving 25 rats divided into five groups: negative control, positive control (CCl₄ without treatment), and three treatment groups administered the extract at doses of 100, 150, and 200 mg/kg body weight for 30 days. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a significance level of p < 0.05. The results showed that the 200 mg/kg dose significantly reduced levels of total cholesterol, triglycerides, and LDL, while the highest increase in HDL was observed at the 100 mg/kg dose. These findings also indicate that the ethanolic extract of Bouea macrophylla fruit exhibits dose-dependent hypolipidemic and antioxidant effects and has potential as a natural therapeutic candidate for improving lipid profile disorders caused by chemically induced liver damage.